Media Sentiment and International Asset Prices - Fraiberger, Samuel P.; Lee, Do; Puy, Damien; Rancier, Romain (World Bank, Washington, DC, 2018)
This paper assesses the impact of media sentiment on international equity prices using a dataset of more than 4.5 million Reuters articles published across the globe between 1991 and 2015. Media sentiment robustly predicts daily returns in both advanced and emerging markets, even after controlling for known determinants of stock prices. But not all news sentiment is alike. A local (country-specific) increase in news optimism (pessimism) predicts a small and transitory increase (decrease) in local returns. By contrast, changes in global news sentiment have a larger impact on equity returns around the world, which does not reverse in the short run. Media sentiment affects mainly foreign -- rather than local -- investors: although local news optimism attracts international equity flows for a few days, global news optimism generates a permanent foreign equity inflow. Our results confirm the value of media content in capturing investor sentiment.